Complications of Cochlear Implant at Hawler Teaching Center (Rizgary Teaching Hospital) - Azhen Ismael Hussen; Arsalan A. Shem (Advanced Medical Journal)
Background and objectives: Cochlear implantation caries many morbidity, complications and even failure which may have an economic burden to candidates and medical administration. Several surgical techniques and implants had been suggested for optimum result and implant proper functioning. Our aim was to determine variouscomplications types and rate encountered in cochlear implantation candidates of different age groups at Rizgary Teaching Hospital.